Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

(−0.75x − 7) − (7.5x + 5.4) simplified

Sagot :

Answer:

[tex]-0.75x-7-7.5x-5.4=-8.25x-12.4[/tex]

Step-by-step explanation:

Given the expression

[tex]\left(-0.75x-7\right)-\left(7.5x+5.4\right)[/tex]

Remove parentheses:   (-a) = -a

[tex]=-0.75x-7-\left(7.5x+5.4\right)[/tex]

As we know that:  - (7.5x + 5.4) = -7.5 - 5.4

[tex]=-0.75x-7-7.5x-5.4[/tex]

Group like terms

[tex]=-0.75x-7.5x-7-5.4[/tex]

Add similar elements:  -0.75x - 7.5x = -8.25x

[tex]=-8.25x-7-5.4[/tex]

Subtract the numbers:  -7 - 5.4 = -12.4

[tex]=-8.25x-12.4[/tex]

Therefore, we conclude that:

[tex]-0.75x-7-7.5x-5.4=-8.25x-12.4[/tex]

We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.